PENGARUH IMPLEMENTASI SHARIA EDUGAME TERHADAP PERFORMANCE LITERACY PENDIDIK TK ISLAM HIDAYATULLAH SEMARANG - Imam Nuryanto; Ida Farida; Guruh Taufan Hariyadi (Jurnal Penelitian Ekonomi dan Bisnis, 2019)
Sharia Edugame is an information technology-based educational media with islamic content. Sharia Edugame is expected to be a learning media that supports early childhood education. Edugame has 7 indicators, namely overall value, usability, accuracy, appropriateness, relevance, objectives and feed back. The purpose of this study was to determine the effect of implementing sharia edugame on educator literacy performance. The object chosen in this study was the TK Islam Hidayatullah Semarang. The sampling technique used was a saturated sample with a total of 21 educators. The data in this study were obtained by questionnaire method which was filled independently. The analysis used in this study uses simple linear regression analysis. The results of this study prove and give the conclusion that the implementation of sharia edugame has a positive and significant effect on performance literacy.Keywords: sharia edugame; islamic content ; performance literacy